1999
DOI: 10.1002/(sici)1521-4141(199904)29:04<1375::aid-immu1375>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

T cell control of staphylococcal enterotoxin B (SEB) lethal sensitivity in mice: CD4+ CD45RBbright / CD4+ CD45RBdim balance defines susceptibility to SEB toxicity

Abstract: Radiation chimeras, generated by transplantation of SCID bone marrow into C3H/HeJ mice, show lethal susceptibility to staphylococcal enterotoxin B (SEB), thus constituting a valid murine model for SEB shock. This SEB sensitivity is due to the ability of the irradiated host to restore residual T cell populations, since the SCID donor bone marrow is unable to generate T cells. SCID bone marrow transplanted into irradiated nude mice does not generate SEB-sensitive chimeras, as a consequence of the inability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Hallmark studies during the 1990s showed that the toxicity of SEB was due to massive T-cell proliferation and proinflammatory cytokine production White et al, 1989). Investigations using T-cell reconstituted immuno-deficient SCID mice confirmed the role of T-cell activation in SE-induced lethality (Miethke et al, 1992;Canaan, et al 1999). Furthermore, these studies indicated that tumor necrosis factor alpha (TNF-) plays a crucial role in SE-induced lethality because passive immunization with an anti-TNF-/ monoclonal antibody protected the animals against an SE challenge (Fast et al, 1989;Miethke et al, 1992).…”
Section: Toxic Shock Syndromementioning
confidence: 98%
“…Hallmark studies during the 1990s showed that the toxicity of SEB was due to massive T-cell proliferation and proinflammatory cytokine production White et al, 1989). Investigations using T-cell reconstituted immuno-deficient SCID mice confirmed the role of T-cell activation in SE-induced lethality (Miethke et al, 1992;Canaan, et al 1999). Furthermore, these studies indicated that tumor necrosis factor alpha (TNF-) plays a crucial role in SE-induced lethality because passive immunization with an anti-TNF-/ monoclonal antibody protected the animals against an SE challenge (Fast et al, 1989;Miethke et al, 1992).…”
Section: Toxic Shock Syndromementioning
confidence: 98%